2018
DOI: 10.1016/j.jmatprotec.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of spatter generation and melt-pool behavior during the powder bed laser beam melting process

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. A B S T R A C TThe experimental analysis of spatter formation was carried out on an instrumented SLM set-up allowing the quantification of spatter ejections and possible correlation with melt-pool behavior. Considering nearly similar SLM conditions than those carried out on SLM machines, an increase of large spatters (> 80 μm) with volume energy density (VED) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(148 citation statements)
references
References 23 publications
12
120
0
1
Order By: Relevance
“…All other parameters were kept constant. Power and speed were chosen so that the ratio power/speed remains constant, in order to theoretically keep the same Volumetric Energy Density (VED), which is ratio of the laser power divided by the scanning speed times the laser spot area, as described by Gunenthiram et al (2018). Such an analytical formulation was used instead of other ones (using for instance powder bed layer or hatch distance as influent parameters) for the following reasons: (1) recent work by Fabbro et al (2018) have shown a linear dependence between fusion depth and such a VED formulation, (2) our experimental results on 316L exhibit a clear dependence between porosity rate (densification level) and such a VED, (3) it provides a physically realistic formulation of laser absorption which occurs mainly at the surface of the melt-pool and is not affected by powder thickness.…”
Section: Materials and Sample Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All other parameters were kept constant. Power and speed were chosen so that the ratio power/speed remains constant, in order to theoretically keep the same Volumetric Energy Density (VED), which is ratio of the laser power divided by the scanning speed times the laser spot area, as described by Gunenthiram et al (2018). Such an analytical formulation was used instead of other ones (using for instance powder bed layer or hatch distance as influent parameters) for the following reasons: (1) recent work by Fabbro et al (2018) have shown a linear dependence between fusion depth and such a VED formulation, (2) our experimental results on 316L exhibit a clear dependence between porosity rate (densification level) and such a VED, (3) it provides a physically realistic formulation of laser absorption which occurs mainly at the surface of the melt-pool and is not affected by powder thickness.…”
Section: Materials and Sample Fabrication Methodsmentioning
confidence: 99%
“…1, coming directly from the powder bed, are entrained upwards by the vapor plume. This effect is known as powder denudation and is in good part at the origin of the spatter formation described by Gunenthiram et al (2018) and Matthews et al (2016). However, this last phenomenon produces discrete particles, with trajectories at a high inclination with the laser beam, so it is not believed to have a continuous and measurable interaction with the laser.…”
Section: Melt Pool Shapementioning
confidence: 99%
“…In laser bed additive manufacturing process, for high energy parameters (high laser power or slow laser speed), the keyhole phenomenon well-known in welding can occur [33,34]. When a massive amount of energy is imposed on a small area, the melt pool becomes narrow and deep which can lead to important solidification defects [35]. Non convex melt pool shape were also reported with Laser Cladding by Biegler et al [7].…”
Section: Epitaxial Grain Growth Along the Thermal Gradientmentioning
confidence: 97%
“…On the other hand, while AlSi10Mg has not been processed by HPT yet, there are vast amount of literature on the HPT processing of other Al-Si-based alloys, e.g. Al-2Si, Al-7Si and Al-12 Si [57][58][59][60]. For example, Wang et al [57] attributed the enhanced hardness and corrosion performance of HPTprocessed Al-7Si to breakage of coarse Si particles and intermetallic phases, microstructure homogeneity and increased active sites due to HPT.…”
Section: Introductionmentioning
confidence: 99%